2014
DOI: 10.1590/0004-2730000003003
|View full text |Cite
|
Sign up to set email alerts
|

Screening of celiac disease in patients with autoimmune thyroid disease from Southern Brazil

Abstract: Objective: The objective of this study was to determine the prevalence of celiac disease (CD) in adults with autoimmune thyroid disease (ATD) from the endocrinology outpatient setting in a university hospital in Southern Brazil. Subjects and methods: From the years 2007 to 2011, 254 patients with ATD were enrolled consecutively, Grave's disease was diagnosed in 143 (56.3%) and Hashimoto's thyroiditis in 111 (43.7%) of them. All patients answered a questionnaire related to symptoms that could be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
9
0
1
Order By: Relevance
“…Thirty-seven papers were read in detail, and 11 were excluded for the following reasons: two studies were duplicates and reported the same data as separate publications (10,11); three studies were not primarily aimed at assessing the association between CD and ATD (12)(13)(14); two studies focused on patients with non-ATD, including thyroid agenesis/ hemiagenesis, or positive antithyroid antibodies of unclear clinical significance (15,16); one study focused on patients with a ''risk'' of CD based on antibodies without any further diagnostic evaluation (17); in two studies, diagnosed CD was based only on patient reports/surveys rather than on serologic or histologic criteria (18,19); and one study was excluded because it was based on a sample with high suspicion for selection bias (20). After an initial peer review, one more relevant paper was identified and included (21). In the end, 27 studies were hence entered into the meta-analysis (Table 1) (8,9,11,.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-seven papers were read in detail, and 11 were excluded for the following reasons: two studies were duplicates and reported the same data as separate publications (10,11); three studies were not primarily aimed at assessing the association between CD and ATD (12)(13)(14); two studies focused on patients with non-ATD, including thyroid agenesis/ hemiagenesis, or positive antithyroid antibodies of unclear clinical significance (15,16); one study focused on patients with a ''risk'' of CD based on antibodies without any further diagnostic evaluation (17); in two studies, diagnosed CD was based only on patient reports/surveys rather than on serologic or histologic criteria (18,19); and one study was excluded because it was based on a sample with high suspicion for selection bias (20). After an initial peer review, one more relevant paper was identified and included (21). In the end, 27 studies were hence entered into the meta-analysis (Table 1) (8,9,11,.…”
Section: Study Selectionmentioning
confidence: 99%
“…Biopsy data and Marsh III. Fifteen studies required Marsh III for the CD diagnosis (11,21,23,(25)(26)(27)(28)(29)(30)33,36,38,39,41,42). The prevalence of CD in these studies was 1.4% [CI 1.0-1.8%].…”
Section: Prevalence Of CD In Atd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation, hyperplasia of crypts and villous atrophy are some of the histological findings, which may regress or disappear with the removal of gluten from the diet (42). The prevalence of CD in the population is approximately 1%, and the prevalence of CD in patients with thyroid autoimmune disease is increased -approximately 1.5-5% (43,44).…”
Section: Bowel Disordersmentioning
confidence: 99%